The The Effects of Storyjumper on Narrative Writing Ability of EFL Learners in Higher Education - Nurlaela Nurlaela; M. Jayadin Ilham; Candra M. Lisabe (Universitas Majalengka, 2022)
Writing is a complex process for the EFL learners. Therefore, it needs appropriate and interesting learning media. This research purposes to evaluate and analyze the effects of storyjumper as a digital learning media towards narrative writing ability of EFL learners. Classroom action research was chosen as research methodology. There were 32 learners in English Department of Universitas Muhammadiyah Luwuk as the participant of this research. Descriptive statistic for the quantitative data and descriptive analysis for the qualitative data was conducted as analyzing technique. The result found that storyjumper gave positive effects toward narrative writing ability of EFL learners. It can be proven from the improvement of test result in narrative writing. In the preliminary test, it was 57.16 as the mean score result, while in the cycle 1 was 68.33, and in the cycle 2 was 75.22. In addition, storyjumper also affected the writing process, namely they did not take a long time for start writing, active participated, and focused on the writing activity. Finally, the storyjumper gave positive effects towards EFL learners in narrative writing test and process.